2019
DOI: 10.46490/vol25iss2pp257
|View full text |Cite
|
Sign up to set email alerts
|

Impact of urban green spaces, native tree species and seasons on soil pH in Kaunas, Lithuania

Abstract: Tree growth is sensitive to soil pH in urban areas and is often higher than in rural forest. However, there are knowledge gaps on how soil pH and alkalization are affected by urban environments and seasonal climate as well as the cascading effects on tree species. In order to fulfill these gaps, we analyzed the soil pHCaCl of four common native deciduous tree species: Acer platanoides, Tilia cordata, Quercus robur and Betula pendula in five different types of urban green spaces in Kaunas city municipality (Lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Low pH values were sporadically recorded, mainly in the soils of urban forests (type B). In cities, a clear shift in the reaction towards alkalisation is the result of alkaline dust precipitation, use of street snow removal agents, and high concentrations of calcium carbonate of anthropogenic origins [35]. A pH value is crucial for the bioavailability of heavy metals to plants, i.e., the increased pH values reduce the risk of entering the food chain by heavy metals [5].…”
Section: Resultsmentioning
confidence: 99%
“…Low pH values were sporadically recorded, mainly in the soils of urban forests (type B). In cities, a clear shift in the reaction towards alkalisation is the result of alkaline dust precipitation, use of street snow removal agents, and high concentrations of calcium carbonate of anthropogenic origins [35]. A pH value is crucial for the bioavailability of heavy metals to plants, i.e., the increased pH values reduce the risk of entering the food chain by heavy metals [5].…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, soil characteristics (such as soil communities, pH, and soil quality) in combination with litter quality may cause different trends in the leaf litter decomposition of different green spaces. Indeed, Straigytė et al [41] found a negative correlation between leaf litter decomposition in peri-urban forests and acidic soils with a low N:P ratio.…”
Section: Leaf Litter C:n C:p and N:p Ratiomentioning
confidence: 99%
“…In addition, previous research has shown that different leaf litter decomposition rates are due to environmental variability. For instance, leaf litter decomposition can be more rapid in urban areas because of higher temperatures, greater nutrient availability (e.g., soil fertilization), and an increased abundance of earthworms, as well as different soil substrate and pH [40][41][42][43]. However, Rawlik et al [44] found that higher soil temperature may lead to reduced moisture and slower leaf litter decomposition.…”
Section: Leaf Litter Decomposition In Different Urban Green Spacesmentioning
confidence: 99%
“…Plant communities in natural and planted forests ("forest phytocenoses") play a key role in mitigating the negative effects of industrialization and climate change (Faucon et al 2016, Burns et al 2017, Straigyte et al 2019, Savosko et al 2020b. Besides, the forest communities provide important ecosystem functions and services such as regulating carbon, nutrient and water cycles, providing timber for industries, wildlife habitat and opportunities for recreation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, forest soil properties have a significant impact on the richness and diversity of plants, the structure and dynamics of plant communities and the development of terrestrial flora (O'Neill et al 2005, Bardule et al 2017, Urbina et al 2017, Savosko et al 2018. On the other hand, plants as a primary factor in soil development, determine the most important soil properties that affect soil resistance to the degradation and pollution as well as sustainable development of soil (Straigyte et al 2019, Naik et al 2020, Pankiv et al 2020. Finally, the plant-soil interactions are a prominent component of the plant communities that responds to envi-ronmental impact.…”
Section: Introductionmentioning
confidence: 99%